2012
DOI: 10.1007/s00441-012-1487-4
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of SATB2 to the stronger osteogenic potential of bone marrow stromal cells from craniofacial bones

Abstract: Previous studies have shown that craniofacial bone marrow stromal cells (BMSCs) have a strong osteogenic potential. However, the mechanism by which BMSCs of various embryonic origins develop diverse osteogenic potentials remains unclear. To investigate the mechanisms regulating osteoblast differentiation in two different types of BMSCs, we compared the temporal and spatial mRNA and protein expression patterns of Satb2 and its downstream gene Hoxa2 by using real-time polymerase chain reaction, Western blotting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…Western blots and real-time PCR analysis were performed as our previous reports [ 43 ]. The primary antibodies used for western blots are listed in Supplementary Table S2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Western blots and real-time PCR analysis were performed as our previous reports [ 43 ]. The primary antibodies used for western blots are listed in Supplementary Table S2 .…”
Section: Methodsmentioning
confidence: 99%
“…All procedures were carried out according to the guidelines of the Animal Care Committee of Nanjing Medical University. As we described previously [ 43 ], BMSCs derived from mandibular were isolated from young group (3 months old), middle-aged group (12 months old) and old group (18 months old) male Sprague-Dawley (SD) rats. 15 months old SD rats were transplanted with green fluorescent protein (GFP) modified or SATB2 enforced BMSCs (1 × 107) by tail vein at week 2, 6, and 12 after micro-CT scan.…”
Section: Methodsmentioning
confidence: 99%
“…[18][19][20] Special AT-rich sequencebinding protein 2 (SATB2) is another factor responsible for osteoblast differentiation of BMSCs. 21 Overexpression of SATB2 promotes osteogenesis and improves bone mass in mice. 22 Genetically modified BMSCs are widely used in bone-tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…SATB2 is an important positive regulator in osteoblast differentiation, bone formation, and bone regeneration ( 17 , 18 ). It has previously been demonstrated that SATB2 was able to repair and regenerate calvarial defects ( 19 ). In addition, SATB2 has also been reported to be expressed in the cortex of the brain, breast tissues, spinal cord, kidneys, umbilical cord, leukocytes and the central nervous system ( 9 , 17 ), which suggests a distinct role of SATB2 in different tissues.…”
Section: Discussionmentioning
confidence: 99%